2019
DOI: 10.1103/physrevb.100.140503
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous charge noise in superconducting qubits

Abstract: We have used Ramsey tomography to characterize charge noise in a weakly charge-sensitive superconducting qubit. We find a charge noise that scales with frequency as 1/f α over 5 decades with α = 1.93 and a magnitude Sq(1 Hz) = 2.9 × 10 −4 e 2 /Hz. The noise exponent and magnitude of the low-frequency noise are much larger than those seen in prior work on single electron transistors, yet are consistent with reports of frequency noise in other superconducting qubits. Moreover, we observe frequent large-amplitude… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 39 publications
2
35
2
Order By: Relevance
“…The QPT rates appear to be extremely slow among all the designs, making the parity switching times exceptionally long, ranging from 1 ms to up to 1.5 s. Thus, the qubits are not significantly disturbed by the QPT events during their average lifetimes. The observed QPT rates are substantially lower than those previously reported elsewhere, in which the parity switching times range between µs to ms [13,16,18,[28][29][30][31][32]. The median of Γ 1 s are at least two orders of magnitude larger than that of QPT rates suggesting that coherence of our standard devices is not currently limited by quasiparticle tunneling events.…”
contrasting
confidence: 60%
See 1 more Smart Citation
“…The QPT rates appear to be extremely slow among all the designs, making the parity switching times exceptionally long, ranging from 1 ms to up to 1.5 s. Thus, the qubits are not significantly disturbed by the QPT events during their average lifetimes. The observed QPT rates are substantially lower than those previously reported elsewhere, in which the parity switching times range between µs to ms [13,16,18,[28][29][30][31][32]. The median of Γ 1 s are at least two orders of magnitude larger than that of QPT rates suggesting that coherence of our standard devices is not currently limited by quasiparticle tunneling events.…”
contrasting
confidence: 60%
“…However, the coherence times of such qubits still need to be enhanced to meet the requirements for the error correction threshold [5,6]. One possible mechanism that can limit the qubit coherence times is the presence of non equilibrium quasiparticles [7][8][9][10][11][12][13][14][15][16][17][18][19][20], which are broken Cooper pairs out of the superconducting condensate at low temperatures. When a quasiparticle tunnels across the Josephson junction (JJ), there is a possibility of exchanging energy with the qubit, leading to depolarization.…”
mentioning
confidence: 99%
“…We anticipate that applying this protocol to even higher level Φ;? ðωÞ (red) measured by performing SL (0, 1) , SL (1,2) transitions (j > 2) of a superconducting qubit sensor will enable one to distinguish other dephasing noise sources, such as charge noise 42 .…”
Section: Discussionmentioning
confidence: 99%
“…As an example, we measured the twofold power spectra of dephasing noise acting on the and transitions of a transmon, and showed that our protocol can distinguish between externally applied, known, engineered noise contributions from flux noise and photon shot noise. We anticipate that applying this protocol to even higher level transitions ( j > 2) of a superconducting qubit sensor will enable one to distinguish other dephasing noise sources, such as charge noise 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Gate charge drift is a known weak spot of superconducting qubits with charge degrees of freedom, and it results in fluctuations of the gate charge bias point on the time scale of minutes [39]. This effect can be compensated for by implementing a suitable feedback mechanism for n G .…”
Section: Technical Aspects: Charge Qubitmentioning
confidence: 99%